Technical report: solving linear and nonlinear ordinary differential equations using variational iteration method / Nurul Fatihah Mohamad Ariffin, Siti Aisyah Afifah Azman and Siti Mariam Sarudin - Mohamad Ariffin, Nurul Fatihah; Azman, Siti Aisyah Afifah; Sarudin, Siti Mariam (2017)
The primary purpose of this study is to apply the variational iteration method (VIM) to solve linear and nonlinear second order ordinary differential equations (ODE). VIM is the chosen method because it does not require linearization of equation. One linear and one nonlinear equation called the Duffing equation are solved by using VIM. In this paper, the approximate solutions for several iterations for both equations are determined. All the workings in this study are computed by using Maple. Graphs and tables are provided to give comparison between the given exact solution and the approximate solution found through VIM. The results show that VIM is an efficient and powerful tool to give accurate solutions to linear and nonlinear second order ordinary differential equations as it gives several successive approximations.